Lecture or Practice, Identifying the Mentoring Model for OSN Classes to Stimulate the Creation of an Engaging and Sustainable Learning Class - Ihtiari Prastyaningrum; Asta Nina Karunia (Faculty of Mathematics and Natural Sciences, University of Jember, 2025)
The National Science Olympiad (OSN) is one of the prestigious science competitions held annually for elementary, junior high, and senior high school students. The main objective of OSN is to scout the best students in science, who will later be prepared to represent Indonesia in various international science Olympiads. So far, the OSN mentoring process has been carried out independently by teachers in their respective schools, such as the OSN mentoring at MIT Bakti Ibu in Madiun City. Based on the results of observations and interviews with the mentoring teacher, several problems are faced in the OSN preparation process, one of which is how to design an engaging OSN learning activity, particularly for Physics. In response to this problem, we collaborated with teachers at MIT Bakti Ibu to conduct intensive mentoring for the preparation of the OSN, starting from the district/city level. Our main focus was on the field of Physics, while Biology was handled by the school's internal team. The mentoring process was carried out by combining several learning models to stimulate student interest. The initial steps of this activity were to identify the existing form of mentoring, the materials used, and the mentoring schedule. The mentoring process was conducted classically, involving five students from the science Olympiad class. The results of the activity show that the science Olympiad students have a great interest when learning is done by directly involving them in a simple science practice. The students also have a deeper understanding when the material is taught through practical sessions. Furthermore, the average evaluation score of the students showed an increase after the intensive mentoring and practical sessions. This proves that practical work is effective in increasing a deep understanding of physics concepts.